"Audacious authenticity". (August 2016) - Cole, Mandy England
"Audacious authenticity" was preached during the Festival of Young Women Preachers held April 7, 2016 in conjunction with the Alliance of Baptists' annual meeting. The two events shared the theme: Bearing in courage, rooted in hope. The Festival is an opportunity for young preachers to receive encouragement and support as each explores her own unique calling. Through this sermon, Reverend England Cole shares her own experience and encourages young preachers to serve in audaciously authentic ways.